2014
DOI: 10.1371/journal.pone.0106693
|View full text |Cite
|
Sign up to set email alerts
|

Non-Invasive Bioluminescence Imaging of β-Cell Function in Obese-Hyperglycemic [ob/ob] Mice

Abstract: BackgroundType 2 diabetes results from failure of the β-cells to compensate for increased insulin demand due to abnormal levels of metabolic factors. The ob/ob(lep-/-) mouse has been extensively studied as an animal model of type 2 diabetes. Previous studies have shown a correlation between β-cell function and bioluminescent imaging in lean genetically engineered mice. The ability to noninvasively monitor β-cell function in ob/ob mice could provide new information on β-cell regulation in type 2 diabetes.Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…The reason for this discrepancy is unclear. Whereas a normalization of the blood glucose levels have been observed in ob / ob mice between 30–50 weeks of age 7 26 27 our data (of unfasted animals) display a more fluctuating pattern, which is in agreement with previous observations in our and other ob / ob colonies. I.e., blood glucose values can vary considerably between individual ob / ob mice in the unfasted state 7 26 28 29 (see Fig.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The reason for this discrepancy is unclear. Whereas a normalization of the blood glucose levels have been observed in ob / ob mice between 30–50 weeks of age 7 26 27 our data (of unfasted animals) display a more fluctuating pattern, which is in agreement with previous observations in our and other ob / ob colonies. I.e., blood glucose values can vary considerably between individual ob / ob mice in the unfasted state 7 26 28 29 (see Fig.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have reported a decline in ob / ob BCV between around 30–48 and 50–56 weeks of age 7 25 . In contrast, our quantitative OPT data and the immunohistochemical analyses of β-cell proliferation indicate that the BCV in ob / ob mice is still expanding at the endpoint of our investigation, i.e.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…However, luciferase needs to be transgenically expressed in these cells, and a secondary imaging modality (e.g., visible light camera, X-ray CT, MRI) is required for anatomical information. Bioluminescence has been utilized in the field of diabetes research by inserting the gene encoding luciferase under control by the mouse insulin promoter (MIP) ( 5 ) enabling non-invasive longitudinal quantification of beta cell mass in the mouse ( 6 ). Similarly, bioluminescence imaging can also be used for more detailed functional assessment of beta cell biology, for example, the technique has been used in pancreatic islet transplantation research, for assessing the level of hypoxia in the engraftment process by expressing luciferase under the control of hypoxia response elements ( 7 ).…”
Section: Imaging Modalitiesmentioning
confidence: 99%